Assessment of Climate Vulnerability on Orange Farming System in Batola - Umi Salawati; Gusti Rusmayadi; Dewi Erika Adriani (Publikasi Indonesia, 2021)
The Siamese orange is a superior commodity because it has economic value and is specific to the characteristics of the tidal swamp agroecosystems. Uncertainty triggered by natural conditions and the market causes farmers to lose money, fail to harvest, and suffer, thus affecting the sustainability of their farming business. The final result of the farmer's business describes the magnitude of the Impact felt by the farmer and the farmer's ability to support the losses that can be experienced. This assessment aims to have a comprehensive CVA (Climate Vulnerability Assessment) for the primary commodities in 3 sub-districts in Batola (Carbon, Mandasatana, and Marabahan) and translate the results of activities with recommendations for these various districts. The research was conducted using survey methods, direct observations in the field, Focus Group Discussions, and in-depth interviews with respondents, namely farmers, traders, as well as community leaders and related agencies (Department of Food Crops and Horticulture (DTPH) and District Agricultural Extension Center) totaling 100 people. The DTPH of Batola Regency also collected secondary data. The data collected were analyzed descriptively. In the district of Cerbon (type A), the highest choice is citrus, then seasonal and mixed crops. The major decisions in the Mandastana sub-district (type B) are monoculture oranges, then seasonal crops, diverse crops, and Galam forest plants. In the Marabahan sub-district (type C), apart from citrus, oil palm and rubber have been developed as industrial support plants